Contemporary Spirituality Crisis and the Urgency of Faith Education: Analysis of Tafsir Tarbawi Qs. Al-Baqarah and Qs. Al-Ikhlas - Siti Lufniyah; Mahyuddin Barni (Tilawah: Journal of Al-Qur'an Studies, 2026)
The contemporary spiritual crisis, characterized by weakening faith, increasing secularism, and the erosion of transcendental values, demands the strengthening of Islamic creed education. This article aims to analyze the urgency of creed education through a tarbawi tafsir study of QS. Al-Baqarah (2):255 and QS. Al-Ikhlas (112):1–4 as theological and pedagogical foundations for faith development. This study employs a qualitative library research method using tahlili and tarbawi approaches, drawing primarily on the tafsir works Fathul Qadir and Al-Jami’ li Ahkam al-Qur’an. The findings reveal that both verses contain essential values of tawhid—rububiyyah, uluhiyyah, and asma’ wa sifat—which serve as a strong foundation for Islamic creed education in responding to modern spiritual crises. These values emphasize the oneness of God, humanity’s absolute dependence on Him, and the formation of holistic spiritual awareness. This article contributes to the development of tarbawi tafsir studies by reaffirming the relevance of Qur’anic monotheistic teachings as a basis for reconstructing contemporary Islamic creed education.